(untitled) (Simbiótica. Revista Eletrônica, 2025)
This article explores the enunciative strategies in the temporal projections of interactive audiovisual works, focusing on those that create the impression that time is controlled by the addressee. The analysis reveals how elements such as art direction, soundtrack, and verbal cues function as expressive articulations that establish temporalities, operating through event markers that indicate the passage of time. The game Braid is the central focus of the analysis, standing out for its inventive use of temporal projections. From the perspective of discursive semiotics, the research shows that these manipulations challenge perception, creating new forms of interaction and enjoyment. By proposing notions of order, meaning, and duration that are detached from the referentiality of the natural world and manipulable by players, these productions create an immersive experience that prompts reflections on the nature of time and its relationship with human experience